Atypical processing of voice sounds in infants at risk for autism spectrum disorder. (October 2015) - Blasi, Anna; Lloyd-Fox, Sarah; Sethna, Vaheshta; Brammer, Michael J.; Mercure, Evelyne; Murray, Lynne; Williams, Steven C.R.; Simmons, Andrew; Murphy, Declan G.M.; Johnson, Mark H.
Abstract: Adults diagnosed with autism spectrum disorder (ASD) show a reduced sensitivity (degree of selective response) to social stimuli such as human voices. In order to determine whether this reduced sensitivity is a consequence of years of poor social interaction and communication or is present prior to significant experience, we used functional MRI to examine cortical sensitivity to auditory stimuli in infants at high familial risk for later emerging ASD (HR group, N = 15), and compared this to infants with no family history of ASD (LR group, N = 18). The infants (aged between 4 and 7 months) were presented with voice and environmental sounds while asleep in the scanner and their behaviour was also examined in the context of observed parent–infant interaction. Whereas LR infants showed early specialisation for human voice processing in right temporal and medial frontal regions, the HR infants did not. Similarly, LR infants showed stronger sensitivity than HR infants to sad vocalisations in the right fusiform gyrus and left hippocampus. Also, in the HR group only, there was an association between each infant's degree of engagement during social interaction and the degree of voice sensitivity in key cortical regions. These results suggest that at least some infants at high-risk for ASD have atypical neural responses to human voice with and without emotional valence. Further exploration of the relationship between behaviour during social interaction and voice processing may help better understand the mechanisms that lead to different outcomes in at risk populations.